2012
DOI: 10.1016/j.pain.2012.07.035
|View full text |Cite
|
Sign up to set email alerts
|

Core outcome measures for opioid abuse liability laboratory assessment studies in humans: IMMPACT recommendations

Abstract: A critical component in development of opioid analgesics is assessment of their abuse liability (AL). Standardization of approaches and measures used in assessing AL has the potential to facilitate comparisons across studies, research laboratories, and drugs. The goal of this report is to provide consensus recommendations regarding core outcome measures for assessing abuse potential of opioid medications in humans in a controlled laboratory setting. Although many of the recommended measures are appropriate for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
67
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(71 citation statements)
references
References 60 publications
2
67
0
2
Order By: Relevance
“…The consistency in the ALERRT ratings by the four laboratory technicians was high but with some of the variability that would be expected under real-world conditions. Drug liking is considered a reliable assessment of the likelihood of abuse of a drug, and human abuse potential studies can be used to analyze the likability of various intact and physically manipulated formulations of drugs (16,17). As drug users attempt to manipulate prescription drugs to change the route of administration and produce greater euphoria (17), a significant increase in time and effort required to achieve maximal euphoria may play a role in decreasing the likelihood of abuse of a given drug formulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The consistency in the ALERRT ratings by the four laboratory technicians was high but with some of the variability that would be expected under real-world conditions. Drug liking is considered a reliable assessment of the likelihood of abuse of a drug, and human abuse potential studies can be used to analyze the likability of various intact and physically manipulated formulations of drugs (16,17). As drug users attempt to manipulate prescription drugs to change the route of administration and produce greater euphoria (17), a significant increase in time and effort required to achieve maximal euphoria may play a role in decreasing the likelihood of abuse of a given drug formulation.…”
Section: Discussionmentioning
confidence: 99%
“…In the United States, overdose with opioids, including heroin, resulted in 28,647 deaths in 2014, with a 14% increase in the age-adjusted rate of drug overdose deaths compared with 2013 (4). Prescription drugs were associated with 22,767 overdose deaths in 2013; 71.3% of these deaths (16,235) involved the use of opioids, the most frequently prescribed drug category in the United States and the most common treatment for chronic pain (3,5).…”
Section: Introductionmentioning
confidence: 99%
“…Further, we examine whether the instruments provide sufficient data regarding cross-sectional reliability and construct validity, longitudinal construct validity (ie, hypothesized relationships between concepts over time), 58 ability to detect change, and responder definitions to meet regulatory standards for assessing benefits and risks in clinical trials. 21,58, 60 We do not review measures for abuse liability assessment in early-phase studies with substance abusers 16 or those designed to predict the development of inappropriate medication use. 14,57 It is important to acknowledge that most instruments reviewed were developed for other purposes (eg, diagnosis of substance use disorders), rather than identifying current inappropriate medication use events occurring in clinical trials.…”
mentioning
confidence: 99%
“…They concluded that: 'The available evidence suggests that opioid analgesics for chronic pain conditions are not associated with a major risk of developing dependence'. The proposition that taking opioids long term for pain compared to taking them for nontherapeutic purposes is markedly less likely to cause a drug use disorder has implications for addiction theory, policy, diagnosis, liability assessment and counseling [10,[22][23][24].…”
mentioning
confidence: 99%